1986
DOI: 10.2466/pms.1986.62.2.467
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Enhancement: A Comparison Study of Biofeedback, Open Focus Training, and Control Procedures

Abstract: Alpha wave production has been related to affective and physiological arousal states since Berger's (1929) initial research. More recently, the possibility of subjects' control of alpha production has been investigated via the innovation of biofeedback procedures. Research conducted by Kamiya in the 1960s and others led to the early conclusion that alpha-wave production could be controlled and that such control could facilitate enhancement of a person's state of physical and psychological well-being. Subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Brown, 1970aBrown, , 1970bHardt & Kamiya, 1978;Kamiya, 1969). However, subsequent reports suggested that the apparent increased alpha trait effect could be correlated with relaxation and selection bias for those who choose to meditate or stay with the practice, and not all meditation studies show an alpha state effect (Aftanas & Golocheikine, 2001;Benson, Malhotra, Goldman, Jacobs, & Hopkins, 1990;Drennen & O'Reilly, 1986;Hebert & Lehmann, 1977;G. D. Jacobs, Benson, & Friedman, 1996;Kwon et al, 1996;Pagano & Warrenburg, 1983;Schuman, 1980;Travis & Wallace, 1999).…”
Section: Continuous Eegmentioning
confidence: 99%
“…Brown, 1970aBrown, , 1970bHardt & Kamiya, 1978;Kamiya, 1969). However, subsequent reports suggested that the apparent increased alpha trait effect could be correlated with relaxation and selection bias for those who choose to meditate or stay with the practice, and not all meditation studies show an alpha state effect (Aftanas & Golocheikine, 2001;Benson, Malhotra, Goldman, Jacobs, & Hopkins, 1990;Drennen & O'Reilly, 1986;Hebert & Lehmann, 1977;G. D. Jacobs, Benson, & Friedman, 1996;Kwon et al, 1996;Pagano & Warrenburg, 1983;Schuman, 1980;Travis & Wallace, 1999).…”
Section: Continuous Eegmentioning
confidence: 99%
“…Brown, 1970b; Hardt & Kamiya, 1978; Kamiya, 1969). However, subsequent reports suggested that the apparent increased alpha trait effect could be correlated with relaxation and selection bias for those who choose to meditate or stay with the practice, and not all meditation studies show an alpha state effect (Aftanas & Golocheikine, 2001; Benson, Malhotra, Goldman, Jacobs, & Hopkins, 1990; Drennen & O’Reilly, 1986; Hebert & Lehmann, 1977; G. D. Jacobs, Benson, & Friedman, 1996; Kwon et al, 1996; Pagano & Warrenburg, 1983; Schuman, 1980; Travis & Wallace, 1999).…”
Section: Eeg and Meditationmentioning
confidence: 99%
“…It has been known for some time that alpha occurs predominantly in the parietal region, has been recorded with average amplitudes ranging 30-50 mV (Kamiya, 1968;Lynch & Paskewitz, 1971), and can be seen in the majority (90%) of the population when resting with eyes closed (Drennen & O'Reilly, 1986) and that opening the eyes can reduce the amount of alpha by 80% or more (Wacker, 1996). However, identifying the specific frequency range of the alpha component of the EEG seems less certain.…”
Section: Target Frequency Rangementioning
confidence: 99%
“…However, identifying the specific frequency range of the alpha component of the EEG seems less certain. For example, previous attempts to enhance alpha using NFT have identified alpha as operating between 7-15 Hz (Brown, 1970), 7.5-13 Hz (Prewett & Adams, 1976), 8-12 Hz (e.g., Albert et al, 1974Cho et al, 2008;Fell et al, 2002), 8.5-12.5 Hz (Bauer, 1976), 8-13 Hz (e.g., Angelakis et al, 2007Hardt & Kamiya, 1978;Nowlis & Kamiya, 1970), 8.5-13.5 Hz (Valle & Levine, 1975), 8-14 Hz (Konareva, 2005, 2006, and 10 Hz AE 1 Hz (Drennen & O'Reilly, 1986). Such inconsistencies in identifying the frequency range of the training component not only make comparisons between studies problematic but also fail to take into account individual differences.…”
Section: Target Frequency Rangementioning
confidence: 99%